LABORATORY EVALUATION OF DIFFERENT BIOPESTICIDES ON FECUNDITY AND DEFORMITY AGAINST LATE INSTAR OF SPODOPTERA LITURA - SAGANE, VINA M.; BARKHADE, U. P. (The Bioscan, 2018)
In present study a laboratory evaluation was conducted to determine the efficacy of different biopesticides viz. SlNPV, Bt, B.bassiana, and their combinations with NSKE 5 % against survivals of 5th instar larvae of Spodopteralitura (Fabricius) to investigate possible effect of these biopesticides on fecundity(eggs/female) and deformity of 5th instar larvae of S. litura. The treatment of combination of SlNPV + NSKE 5% recorded highest (80.00%) pupal deformity followed by SlNPV (72.72%) and B.bassiana + NSKE 5%(66.67 %).The treatment of SlNPV + NSKE 5% recorded highest (85.71%) adult deformity followed by SlNPV (77.78%) and B.bassiana + NSKE 5%(72.72%).The lowest fecundity i.e 206 eggs/female recorded in treatment of SlNPV + NSKE 5% followed by B.bassiana + NSKE 5%( 360 eggs/female) and Bt + NSKE 5%(390 eggs/female).Neem Seed Kernel extract 5% could interfere with protein metabolism of the insect and showed better results when combined with biopesticides than its sole application.